2022
DOI: 10.5530/pj.2022.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Active Fraction of Zingiber officinale Roscoe, Zingiber montanum (J.Koenig) Link ex A., and Zingiber zerumbet (L.) Roscoe ex Sm. Against Propionibacterium acnes

Abstract: MATERIALS AND METHODS MaterialsThe plant material used was taken from Ciamis Regency, West Java Province, Indonesia. Crops were harvested on March 24, 2021 and then determined. Voucher specimens are stored at the Bandungense Herbarium, Bandung Institute of Technology, with registration numbers: Zingiber officinale Roscoe namely FIPIA-DEP30, Zingiber montanum (J.Koenig) Link ex A., namely FIPIA-DEP29 and Zingiber zerumbet (L.) Roscoe ex Sm. , namely FIPIA-DEP27. The bacteria used were Propionibacterium acne ATC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Peaks 20 and 22 were finally identified as ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-ol ( 20 ) and ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-yl acetate ( 22 ), respectively [ 52 ]. These identifications were consistent with previous studies [ 25 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Peaks 20 and 22 were finally identified as ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-ol ( 20 ) and ( E )-4-(3′,4′-dimethoxyphenyl)but-3-en-1-yl acetate ( 22 ), respectively [ 52 ]. These identifications were consistent with previous studies [ 25 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 94%
“…Previous studies have shown that essential oils obtained through the hydrodistillation of plai contained phenylbutenoid monomers [ 26 ], and the ethyl acetate fraction of the 70% ethanol extract of plai contained phenylbutenoid monomers and dimers [ 33 ]. Therefore, herein, the dried rhizomes of two plai samples purchased in Thailand and Indonesia were extracted using ethyl acetate, and then the extracts were subjected to GC–MS ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study done by Farouk et al, myristicin was identified as the major constituents in parsley volatiles analyzed by HS-SPME which support its detection in parsley 41 . Frambinone is a phenolic compound detected in Zingiber officinale and Zingiber montanum and is known for its antibacterial activity 42 .…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical screening showed that the tea with various ginger formulation has positive result on the presence of alkaloids, flavonoids, phenols, tannins and terpenoids. According to Aji et al (2022), the hydro ethanolic extract of Zingiber officinale contain positive result on alkaloid, flavonoid and triterpenoid. Osabor et al (2015) reported that aqueous extract of Zingiber officinale contain positive result on cardiac glycoside, alkaloid, flavonoid, polyphenol and reducing sugars.…”
Section: Phytochemical Screeningmentioning
confidence: 99%